Peltier module in effect to extract safe water from atmospheric moisture powered by solar photovoltaic renewable energy system with contribution from Piezo-materials - Imran, Mohammed Thushar; Barshan, Azraf Nafi; Shams, Sharif Mohd; Tajwar, Rahat (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.